Adapting Iraqi Law to Smart Contracts: A Comparative Analysis Incorporating Islamic Law Principles and Consumer Protection in the Contemporary Digital Era - Mahmood Alaloosh; Govar Majed Ahmad; Lara Adel Jabbar (MILRev: Metro Islamic Law Review, 2026)
This paper analyzes the opportunities and obstacles to introducing smart contracts into the Iraqi legal framework, focusing on the doctrinal and practical aspects. Smart contracts are self-executing transactions based on blockchain networks, lacking the involvement of intermediaries, and contest the concepts of consent, lawful subject matter, and cause of action in traditional civil-law regimes, as embodied in the Iraqi Civil Contracts Law No. 40 of 1951. Using a descriptive-analytical and comparative research approach, the study assesses Iraqi laws, as well as the experience of other countries, specifically the United States, the European Union, and the United Arab Emirates, in relation to legal recognition, assigning liability, consumer protection, and automated implementation. The conclusions show that the current legal system in Iraq lacks express clauses addressing smart contracts, leading to confusion about the identification of parties, their binding relationships, and penalties for programming errors. A comparative analysis shows that effective regulatory models are characterized by clear legal definitions, judicial capacity-building, regulatory sandboxes, and consumer rights protection. The analysis also draws on Islamic normative concepts (maqāṣid al-sharīʿah), such as ḥifẓ al-māl (wealth preservation), al-ʿadl (justice), and darʾ al-mafsid (hitting back), to support ethical governance, algorithmic responsibility, and risk avoidance. On this basis, the study suggests a balanced legislative framework for Iraq that would uphold classical principles of contract keeping and empower digital innovation by introducing statutory treatment of smart contracts, well-structured liability rules, consumer protection, and institutional reforms. Such a framework promotes the responsible adoption of automated contracts in sectors including e-commerce and financial services, enhances legal predictability, aligns domestic law with cross-border digital practices, and ensures normative legitimacy within an Islamic and international legal context.